Endophyte-Derived Natural Products Using In silico and In vitro Methods for Drug Lead Discovery-A Review - Jugguru, Surendra; Chatakondu, Raju; Singarapalle, Shobha; Thirunalveli, Praveena (Pharmacognosy Reviews)
Numerous fungal endophytes produce plant-derived chemicals that are pharmacologically useful, making them well-known sources of naturally occurring, biologically active compounds. Alkaloids, coumarins, flavonoids, glycosides, lignans, phenylpropanoids, quinones, saponins, terpenoids, and xanthones, all produced by endophytic fungi, are common plant-derived therapeutic chemicals included in this study. This overview covers research from the initial discovery of Taxol production by endophytic Taxomyces andreanae in 1993 to mid-2020. The study also discusses the challenges to commercializing this innovative approach in drug development, while emphasizing the significant potential for endophyte-based production of such pharmacologically active chemicals derived from plants. This potential offers an optimistic outlook for future drug development. Thanks to recent advances in the "omics" and "one strain many compounds" (OSMAC) methodologies, fungal endophytes have become powerful alternatives to traditional methods.
Keywords: Alkaloids; Drug Development; Flavonoids; Glycosides; Lignans; Phenylpropanoids; Quinones; Saponins; Secondary Metabolites; Terpenoids; Xanthones; Taxol.